PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) DAN DAMPAKNYA TERHADAP REAKSI INVESTOR - Yuliana, Rita; Purnomosidhi, Bambang; Sukoharsono, Eko Ganis (UI Scholars Hub, 2008)
Recently, Corporate Social Responsibility (CSR) idiom can be easily found in many accounting literatures. It refers to the idea that the firm could not be separated with its environment. CSR is the responsibility o f business organization to involve in protecting environment and social welfare. In fact, many firm s in Indonesia have already applied the disclosure o f CSR, even ju st in a simple ways. The objective o f this research are: (1) to identify the corporate/ firm characteristics including corporate/ firm size, profitability, size o f the board o f commissioners, and public ownership influences to the depth o f CSR disclosure, (2) to determine the impact o f CSR disclosure to investor reaction influences in terms o f abnormal return and trading volume activity. The sample o f this research are 116firm s listed in Indonesia Stock Exchange. Partial Least Square (PLS) is used to test the hypothesis. Based on data analysis, I fin d that the firm characteristics, including profile and public ownership have a significant positive influence on CSR disclosure. And also, this research shows that the scope o f CSR disclosure has a significant influence on investors reactions.